PROBLEMATIKA BAHASA INDONESIA KETERAMPILAN MENYIMAK DI SEKOLAH DASAR - Nur Fatihah, Salma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Listening skills are one of the basic competencies in learning Indonesian whichplays an important role in developing overall language skills. However, in practice, listening skills often experience various problems from the side of students, educators, and learning media. This study aims to identify the problems that arisein listening skills at the elementary school level. The method used is research that comes directly to the school to see how the problems of listening skills are carried out in schools. The results of the study indicate that low student interest in learning, lack of interesting learning media, lack of listening strategies, and listening learning approaches that are not yet varied are the main factors that hinder. Innovation in teaching methods and the use of interactive media are needed to increase the effectiveness of listening learning. This study is expected to be a reference for educators and curriculum developers in designing effective and enjoyable learning strategies.